A microvertebrate assemblage from the Adamantina Formation (Bauru Group, Upper Cretaceous) in São Paulo State, Brazil - Freitas, Rodrigo C. [UNESP]; Batezelli, Alessandro; Muniz, Fellipe P.; Ribeiro, Douglas C. [UNESP]; Ruiz, Juan V. [UNESP]; Alves, Yuri M.; Geroto, Caio; Castro, Mariela C.; Barbosa, Gabriel G. [UNESP]; Langer, Max C.; Montefeltro, Felipe C. [UNESP] (Elsevier, 2023)
The Adamantina Formation is the most extensive and taxonomically rich unit within the Bauru Group (Upper Cretaceous). This unit is considered one of the most complete fossil records of vertebrate continental communities during the Cretaceous Gondwanan landmasses. However, this important fossil record is mainly based on large and articulated remains, and few works attempted to better understand its microvertebrate assemblages. This study reports a diverse microvertebrate assemblage from a new site in the Adamantina Formation in São Paulo, Brazil. The geological context in which the fossils were collected was analyzed, and all fossils were recovered in channel facies of the outcrop. The fossil assemblage described here includes elements commonly found in previous works in the Adamantina Formation, such as lepisosteiforms, amiids, dinosaurs, and crocodyliforms. But in this assemblage were also identified elements rarely recovered from Adamantina Formation, such as siluriforms, anurans, and a putative mammal. Furthermore, the taxa identified here indicate a humid environment, contributing to recognizing a diversity of paleoenvironments in the Adamantina Formation and highlighting the importance of microvertebrate assemblages to understanding the paleoecological aspects of fossil communities.
Keywords: Anura; Bauru Basin; Mammal; Peirosauridae